2018
DOI: 10.1080/08998280.2018.1482519
|View full text |Cite
|
Sign up to set email alerts
|

Dengue fever as a cause of perimyocarditis and low-pressure cardiac tamponade

Abstract: We describe a case of dengue shock syndrome, perimyocarditis, and low-pressure cardiac tamponade following a trip to the Caribbean. The case was managed in the critical care unit and 6 weeks after discharge the patient was asymptomatic with a normal ejection fraction. Dengue fever presenting as cardiac tamponade is exceedingly rare and emphasizes the importance of taking a thorough travel history as well as being aware of atypical manifestations of rare diseases to make a correct diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Perimyocarditis refers to acute pericarditis with elevated troponin and LV ejection fraction less than 55% [ 6 ]. Shah et al reported a case of DENV infection in a young female, complicated by perimyocarditis and cardiac tamponade [ 7 ]. Another case of DENV infection in a young male presenting with hypotension was diagnosed as perimyocarditis later on [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perimyocarditis refers to acute pericarditis with elevated troponin and LV ejection fraction less than 55% [ 6 ]. Shah et al reported a case of DENV infection in a young female, complicated by perimyocarditis and cardiac tamponade [ 7 ]. Another case of DENV infection in a young male presenting with hypotension was diagnosed as perimyocarditis later on [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 22% of fatal CHIK cases are caused by cardiovascular diseases, with heart failure being the most common. The most commonly reported abnormality in the electrocardiograms of patients with CHIK is the inversion of T waves in leads DII, III, aVF, V5-V6, and elevation of the ST segment [20][21][22] . Most patients who do not die from acute cardiac involvement completely recover; however, case reports show that cardiovascular compromise can cause subacute and chronic illness, emphasizing the need for longitudinal recognition and management of patients with atypical CHIK 23,24 .…”
Section: Cardiovascular Manifestationsmentioning
confidence: 99%